2006
DOI: 10.1073/pnas.0510857103
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-specific mutations in PIK3CA are oncogenic in vivo

Abstract: The PIK3CA gene, coding for the catalytic subunit p110␣ of class IA phosphatidylinositol 3-kinases (PI3Ks), is frequently mutated in human cancer. Mutated p110␣ proteins show a gain of enzymatic function in vitro and are oncogenic in cell culture. Here, we show that three prevalent mutants of p110␣, E542K, E545K, and H1047R, are oncogenic in vivo. They induce tumors in the chorioallantoic membrane of the chicken embryo and cause hemangiosarcomas in the animal. These tumors are marked by increased angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
302
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(322 citation statements)
references
References 32 publications
16
302
2
2
Order By: Relevance
“…[26][27][28][29] However, it has been reported that chickens injected with exon 20 PIK3CA mutants developed larger tumors than those injected with exon 9 PIK3CA mutants. 30 The distinct associations of the different PIK3CA mutations with histologic type, grade, and depth of myometrial invasion in endometrial carcinomas is consistent with the idea that different categories of mutants, defined by their structural and functional domains, would increase PI3K function by diverse mechanisms. Mutations in the kinase domain of exon 20 alter the catalytic loop and increase the specific activity of the enzyme, thus enhancing pathway activation.…”
Section: Discussionsupporting
confidence: 75%
“…[26][27][28][29] However, it has been reported that chickens injected with exon 20 PIK3CA mutants developed larger tumors than those injected with exon 9 PIK3CA mutants. 30 The distinct associations of the different PIK3CA mutations with histologic type, grade, and depth of myometrial invasion in endometrial carcinomas is consistent with the idea that different categories of mutants, defined by their structural and functional domains, would increase PI3K function by diverse mechanisms. Mutations in the kinase domain of exon 20 alter the catalytic loop and increase the specific activity of the enzyme, thus enhancing pathway activation.…”
Section: Discussionsupporting
confidence: 75%
“…Another mutation that has been studied functionally (H1047R; refs. [16][17][18][19][20] was not found in our study; however, we found a mutation that changed the amino acid at the same position (H1047Y). Thus, for many mutations in the current study, there are data supporting a functional role in oncogenesis.…”
Section: Discussioncontrasting
confidence: 67%
“…Several of the mutations found in our study (E542K, E545K, and M1043I) are oncogenic or increase kinase activity, albeit in nongliomatous systems (16)(17)(18)(19)(20). Another mutation that has been studied functionally (H1047R; refs.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, expression of the mutant PIK3CA increases PI3K activity and has been shown to be transforming (Bader et al, 2006;Horn et al, 2008;Zhang et al, 2008). Therefore, it is important to elucidate mechanisms that lead to expression of these activating mutants.…”
Section: Mda-mb-231mentioning
confidence: 99%
“…In addition, gene deletion studies in mice have shown that p110a is essential for growth factor signaling as well as for oncogenic transformation (Zhao et al, 2006), whereas direct interaction of Ras with p110a is required for oncogenic Ras-induced tumorigenesis (Gupta et al, 2007). Moreover, activating PIK3CA mutations, observed in many different cancers, are also shown to be transforming (Bader et al, 2006;Horn et al, 2008;Zhang et al, 2008) and increased expression of mutant PIK3CA further induces PI3K activity . All these studies indicate the importance of p110a in cancer and the significance of understanding the mechanisms that lead to its expression.…”
Section: Introductionmentioning
confidence: 99%